Positive electrode sheet for secondary battery and secondary battery

By adding evenly distributed single-wall carbon nanotubes and lithium iron phosphate to the positive electrode sheet of the lithium secondary battery, a three-dimensional conductive network structure is formed, which solves the problem of insufficient conductivity of the positive electrode material, and reduces charge and discharge DCR and improves electricity The effect of core safety performance.

CN115799452BActive Publication Date: 2025-02-18XIAMEN KNANO GRAPHENE TECH CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211536693.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-02
Publication Date
2025-02-18
Estimated Expiration
2042-12-02

AI Technical Summary

Technical Problem

In existing lithium secondary batteries, the conductivity of the positive electrode material is insufficient, resulting in a high charge and discharge direct current impedance (DCR) of the battery, affecting energy efficiency, cycle life and safety.

Method used

A uniformly distributed single-walled carbon nanotube (SWCNT) and lithium iron phosphate are added to the positive electrode sheet. By adjusting the weight ratio, specific surface area and tube length distribution width of the SWCNT, a three-dimensional conductive network structure with excellent conductivity is formed.

Benefits of technology

The resistance of the positive electrode sheet is reduced, the conductivity is improved, the charge and discharge DCR is reduced, the discharge efficiency is improved, the temperature rise is reduced, and the safety performance of the battery cell is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115799452B_ABST
    Figure CN115799452B_ABST
Patent Text Reader

Abstract

The present application relates to the field of battery technology, and in particular to a positive electrode sheet for a secondary battery and a secondary battery, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material coated on the surface of the positive electrode current collector, wherein the positive electrode active material comprises lithium iron phosphate and single-walled carbon nanotubes, wherein the single-walled carbon nanotubes are dispersed in the lithium iron phosphate of the positive electrode sheet, and part of the single-walled carbon nanotubes are attached to the surface of lithium iron phosphate particles; the weight proportion A of the single-walled carbon nanotubes, the specific surface area BET of the single-walled carbon nanotubes in the positive electrode sheet, and the tube length distribution width D of the single-walled carbon nanotubes satisfy the following relationship: 1.8≤100A*BET / D≤23.5; the unit of the specific surface area BET of the single-walled carbon nanotubes is m 2 / g, wherein the weight proportion A of the single-walled carbon nanotubes refers to the weight proportion of the single-walled carbon nanotubes in the positive electrode sheet portion excluding the positive electrode current collector. The present application can significantly improve discharge performance and reduce temperature rise, thereby improving the safety performance of the battery cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet for a secondary battery and a secondary battery. Background Art

[0002] Lithium secondary batteries are widely used in electronic products, aerospace, energy vehicles and other fields, and are one of the most important new energy sources. During the charging process, lithium ions are released from the positive electrode material, transferred to the negative electrode through the electrolyte, and embedded in the negative electrode carbon material; at the same time, electrons are released from the positive electrode and reach the negative electrode from the external circuit to maintain the balance of the chemical reaction. During the discharge process, lithium ions are released from the negative electrode and reach the positive electrode through the electrolyte. At the same time, the negative electrode releases electrons and reaches the positive electrode from the external circuit to provide energy to the outside world. The conductivity of the positive electrode material in the lithium secondary battery directly affects the battery's charge and discharge DCR (Direct Current Resistance), which in turn affects the energy efficiency, cycle life and safety of the lithium secondary battery. Existing lithium secondary batteries usually use conductive agents such as carbon black and graphene to reduce the internal resistance of the positive electrode sheet, but when using the above conductive agents, lithium ions need to bypass large-size conductive agent particles during the interface diffusion process, the diffusion path is long, the resistance is high, and it is not conducive to battery performance. Summary of the invention

[0003] In view of the above problems in the prior art, the present application provides a positive electrode sheet for a secondary battery and a secondary battery, and the specific technical solutions are as follows:

[0004] On the one hand, the present application provides a positive electrode plate for a secondary battery, the positive electrode plate comprising a positive electrode current collector and a positive electrode active material coated on the surface of the positive electrode current collector, the positive electrode active material comprising lithium iron phosphate and single-walled carbon nanotubes, the single-walled carbon nanotubes are dispersed in the lithium iron phosphate of the positive electrode plate, and part of the single-walled carbon nanotubes are attached to the surface of the lithium iron phosphate particles;

[0005] The weight proportion A of the single-walled carbon nanotubes, the specific surface area BET of the single-walled carbon nanotubes in the positive electrode sheet, and the tube length distribution width D of the single-walled carbon nanotubes satisfy the following relationship: 1.8≤100A*BET / D≤23.5, wherein the weight proportion A of the single-walled carbon nanotubes refers to the weight proportion of the single-walled carbon nanotubes in the positive electrode sheet portion excluding the positive electrode current collector;

[0006] The unit of the specific surface area of ​​the single-walled carbon nanotube BET is m 2 / g.

[0007] Specifically, the tube length distribution width D of the single-walled carbon nanotubes is obtained by the following formula: D = (D3-D1) / D2;

[0008] Wherein, D1 represents the sheet diameter corresponding to the cumulative volume proportion of the single-walled carbon nanotubes used in the positive electrode sheet in the NMP solvent reaching the first preset proportion, D2 represents the sheet diameter corresponding to the cumulative volume proportion of the single-walled carbon nanotubes used in the positive electrode sheet in the NMP solvent reaching the second preset proportion, and D3 represents the sheet diameter corresponding to the cumulative volume proportion of the single-walled carbon nanotubes used in the positive electrode sheet in the NMP solvent reaching the third preset proportion, and the first preset proportion, the second preset proportion and the third preset proportion increase in sequence;

[0009] The tube length of the single-walled carbon nanotube satisfies at least one of 0.1≤D1≤1.2 μm, 3≤D2≤8 μm and 10≤D3≤25 μm.

[0010] Specifically, the tube length distribution width D of the single-walled carbon nanotubes satisfies 3.4≤D≤8.3.

[0011] Specifically, the weight proportion A of the single-walled carbon nanotubes satisfies 0.03%≤A≤0.10%.

[0012] Specifically, the specific surface area BET of the single-walled carbon nanotubes in the positive electrode sheet satisfies 500≤BET≤800m 2 / g.

[0013] Specifically, the diameter of the single-walled carbon nanotubes in the positive electrode plate is 1-5 nm.

[0014] Specifically, the adhesive in the positive electrode plate includes one or more of PVDF, PVA, PTFE and PAA.

[0015] Optionally, the weight proportion A of the single-walled carbon nanotubes, the specific surface area BET of the single-walled carbon nanotubes in the positive electrode plate and the tube length distribution width D of the single-walled carbon nanotubes satisfy the following relationship: 4≤100A*BET / D≤15.

[0016] Specifically, the lithium iron phosphate in the positive electrode plate is nano lithium iron phosphate.

[0017] On the other hand, the present application provides an electrode, which includes the positive electrode plate as described above.

[0018] On the other hand, the present application provides a secondary battery, which includes the positive electrode sheet as described above.

[0019] On the other hand, the present application provides an electronic device, which includes the positive electrode sheet or the secondary battery as described above.

[0020] Based on the above technical solution, this application has the following beneficial effects:

[0021] By adding lithium iron phosphate with uniformly distributed SWCNTs into the positive electrode sheet and clarifying the relationship between the weight proportion of SWCNTs, the tube length distribution width and the specific surface area and their corresponding value range, a three-dimensional conductive network structure with excellent conductivity can be formed in the electrode sheet, reducing the electrode sheet resistance, synergistically improving the conductive performance of the positive electrode sheet, reducing the charge and discharge DCR, improving the discharge efficiency and reducing the temperature rise, and improving the safety performance of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings required for use in the embodiments or prior art descriptions. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 is a SEM image of the positive electrode active material of the positive electrode sheet provided in the embodiment of the present application;

[0024] Figure 2 It is the 25°C rate discharge temperature rise curve of Examples 1 to 3 of the present application and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0026] For the following defined terms, these definitions shall apply unless a different definition is given in the claims or elsewhere in this specification. All numerical values, whether or not explicitly indicated, are defined herein as modified by the term "about". The term "about" generally refers to a numerical range that a person of ordinary skill in the art considers to be equivalent to the stated values ​​to produce substantially the same properties, functions, results, etc. A numerical range indicated by a lower value and a higher value is defined to include all numerical values ​​included in the numerical range and all subranges included in the numerical range.

[0027] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.

[0028] The following introduces a positive electrode plate for a secondary battery provided in an embodiment of the present application. The positive electrode plate includes a positive electrode collector and a positive electrode active material coated on the surface of the positive electrode collector. The positive electrode active material includes lithium iron phosphate and single-walled carbon nanotubes. The single-walled carbon nanotubes are dispersed in the lithium iron phosphate of the positive electrode plate, and some of the single-walled carbon nanotubes are attached to the surface of the lithium iron phosphate particles; wherein the positive electrode active material is coated on at least one surface of the positive electrode collector.

[0029] Specifically, the single-walled carbon nanotubes (SWCNTs) used in the positive electrode include SWCNTs of different tube lengths, and some SWCNTs with longer tube lengths can be coated on the surface of lithium iron phosphate particles to inhibit and alleviate the volume expansion of lithium iron phosphate particles during charging and discharging. SWCNTs of different tube lengths form a three-dimensional conductive network structure in the positive electrode active material.

[0030] In some embodiments, the lithium iron phosphate in the positive electrode active material is nano lithium iron phosphate. Specifically, the sheet size distribution of lithium iron phosphate satisfies 100≤D10≤600nm, wherein D10 refers to the secondary particle size corresponding to when the cumulative volume percentage of lithium iron phosphate in an aqueous solvent reaches 10%. Specifically, the surface of lithium iron phosphate is coated with carbon, and the surface coating carbon content C satisfies 0.5%≤C≤2.5%. In this way, controlling the particle size and carbon content of lithium iron phosphate within the above range can enable single-walled carbon nanotubes to form an effective coating and intersperse in the gaps between lithium iron phosphate particles, thereby effectively suppressing the volume expansion of lithium iron phosphate.

[0031] In some embodiments, the positive electrode current collector may include but is not limited to at least one of carbon-coated aluminum foil, carbon-coated copper foil, carbon-coated gold foil, carbon-coated aluminum alloy foil, or carbon-coated composite current collector.

[0032] The weight proportion A of the single-walled carbon nanotubes, the specific surface area BET of the single-walled carbon nanotubes in the positive electrode sheet and the tube length distribution width D of the single-walled carbon nanotubes satisfy the following relationship: 1.8≤100A*BET / D≤23.5; the specific surface area BET of the single-walled carbon nanotubes is in m 2 / g. The weight proportion A of the single-walled carbon nanotubes refers to the weight proportion of the single-walled carbon nanotubes in the positive electrode sheet after the positive electrode current collector is removed, that is, if the weight of the positive electrode sheet after the current collector is removed is Y, and the weight of the single-walled carbon nanotubes is X, then A=X / Y.

[0033] In this way, by adding lithium iron phosphate with uniformly distributed SWCNTs into the positive electrode sheet and clarifying the relationship between the weight proportion of SWCNTs, the tube length distribution width and the specific surface area and their corresponding value range, a three-dimensional conductive network structure with excellent conductivity can be formed in the electrode sheet, reducing the electrode sheet resistance, synergistically improving the conductive performance of the positive electrode sheet, reducing the charge and discharge DCR, improving the discharge efficiency and reducing the temperature rise, and improving the safety performance of the battery cell.

[0034] Specifically, by adopting the above technical scheme, the resistance of the positive electrode plate after cold pressing reaches below 0.62Ω, and the secondary battery adopting the above positive electrode plate has a discharge DCR of below 39.8Ω at 25℃ / 50%SOC, a discharge DCR of below 96.5Ω at 0℃ / 50%SOC, a discharge capacity of above 89.5mAh / g at 0℃ / 3C, and a discharge energy efficiency of above 89.4% at 25℃ / 3C.

[0035] In some embodiments, the weight proportion A of the single-walled carbon nanotubes, the specific surface area BET of the single-walled carbon nanotubes in the positive electrode sheet, and the tube length distribution width D of the single-walled carbon nanotubes satisfy the following relationship: 4≤100A*BET / D≤15. In this way, by further optimizing the value range of the above relationship between A, BET and D, the resistance of the cold-pressed positive electrode sheet can be further optimized to less than 0.52Ω. The secondary battery using the above positive electrode sheet has a discharge DCR of less than 35.2Ω at 25℃ / 50%SOC, a discharge DCR of less than 87.3Ω at 0℃ / 50%SOC, a discharge capacity of more than 90.1mAh / g at 0℃ / 3C, and a discharge energy efficiency of more than 92.1% at 25℃ / 3C.

[0036] In the embodiments of the present application, the lower limit value of 100A*BET / D may include the following values: 1.8, 2.0, 3.0, 4.0 or 5.0, etc.; the upper limit value of 100A*BET / D may include the following values: 23.5, 20, 18.5, 16.5 or 15, etc.

[0037] In some embodiments, the tube length distribution width D of the single-walled carbon nanotube is obtained by the following formula, D = (D3-D1) / D2; wherein D1 represents the sheet diameter corresponding to the cumulative volume proportion of the single-walled carbon nanotubes used in the positive electrode sheet in the NMP solvent reaches the first preset proportion, D2 represents the sheet diameter corresponding to the cumulative volume proportion of the single-walled carbon nanotubes used in the positive electrode sheet in the NMP solvent reaches the second preset proportion, and D3 represents the sheet diameter corresponding to the cumulative volume proportion of the single-walled carbon nanotubes used in the positive electrode sheet in the NMP solvent reaches the third preset proportion, and the first preset proportion, the second preset proportion and the third preset proportion increase in sequence. Specifically, the first preset proportion is 80%-95%, preferably 90%, the second preset proportion is 45%-60%, preferably 50%, and the third preset proportion is 5%-15%, preferably 10%. Specifically, the sheet diameter of the single-walled carbon nanotube here refers to the tube length of the single-walled carbon nanotube.

[0038] In some embodiments, the tube length D1 of the single-walled carbon nanotube satisfies 0.1≤D1≤1.2μm, preferably, D1 satisfies 0.3≤D1≤1.0μm, and more preferably, D1 satisfies 0.4≤D1≤0.8μm; the tube length D2 of the single-walled carbon nanotube satisfies 3≤D2≤8μm, preferably, D2 satisfies 4≤D2≤7μm, and more preferably, D2 satisfies 4.5≤D2≤7μm; the tube length D3 of the single-walled carbon nanotube satisfies 10≤D3≤25μm, preferably, D3 satisfies 10≤D3≤25μm, and more preferably, D3 satisfies 10≤D3≤25μm. By setting D1, D2 and D3 to the above range, a reasonable particle size distribution of SWCNT in lithium iron phosphate is ensured, and SWCNT is ensured to form a sufficient amount of long-range conductive and short-range conductive structures in the electrode system, thereby forming a three-dimensional conductive network structure with rich scale parameters, improving the conductivity of the electrode sheet, and reducing the internal resistance. Specifically, SWCNTs of D1 size can ensure the "point-line" conductive structure between LFP particles, realize short-range conduction, and can replace the "point-line" conductive structure of traditional conductive carbon black; SWCNTs of D2 size can ensure the long-range conductive structure in the electrode; SWCNTs of D3 size can ensure the surface wrapping structure of SWCNT on LFP particles, inhibiting the volume expansion of LFP.

[0039] In some embodiments, the tube length distribution width D of the single-walled carbon nanotubes satisfies 3.4≤D≤8.3. Specifically, the lower limit of the tube length distribution width D of the single-walled carbon nanotubes may include the following values: 3.4, 3.9 or 4.5, etc.; the upper limit of the tube length distribution width D of the single-walled carbon nanotubes may include the following values: 8.3, 7.6 or 7, etc. In the case where the tube length distribution width D of the single-walled carbon nanotubes is too small (such as less than 3.4), the tube lengths of the single-walled carbon nanotubes are similar, which is not conducive to the formation of long-range and short-range conductive structures, and is not conducive to the formation of effective coating of lithium iron phosphate materials; in the case where the tube length distribution width D of the single-walled carbon nanotubes is too wide (such as greater than 8.3), the tube length distribution range of the single-walled carbon nanotubes is too wide, which will cause different microcurrent flow rates at different positions in the positive electrode sheet, affecting the rate discharge performance. By setting the tube length distribution width D of the single-walled carbon nanotubes to the above value, it is possible to ensure that a reasonable spatial building structure is formed in the positive electrode active material to form point-line short-range conduction and long-range conduction with the LFP particles it contains, and a multi-dimensional conductive network structure with sufficient electron transmission channels and ion diffusion channels.

[0040] In this way, by setting D, D1, D2 and D3 to the above range, the reasonable particle size distribution of SWCNT in lithium iron phosphate is ensured, the conductive space structure is further optimized, a good conductive network is formed for conducting electrons, and sufficient ion diffusion channels are formed to ensure sufficient infiltration of the electrolyte and provide channels for liquid phase ion conduction.

[0041] In some embodiments, the weight percentage A of the single-walled carbon nanotubes satisfies 0.03%≤A≤0.10%. Specifically, the lower limit of the weight percentage A of the single-walled carbon nanotubes may include the following values: 0.03%, 0.04% or 0.05%, and the upper limit of the weight percentage A of the single-walled carbon nanotubes may include the following values: 0.10%, 0.09% or 0.08%. When the weight percentage A of the single-walled carbon nanotubes is too small (for example, less than 0.03%), it is impossible to achieve effective conductivity enhancement, and the ion diffusion requirements cannot be met, thereby affecting the battery performance; when the weight percentage A of the single-walled carbon nanotubes is too high (such as greater than 0.10%), it is impossible to form an effective three-dimensional conductive network, and the ion channels formed are relatively small, and the production cost is increased. By controlling the weight percentage A of the graphene quantum dots in the positive electrode sheet to the above range, the electron transmission channel and ion diffusion channel of the positive electrode sheet can be ensured, and the resistance of the electrode sheet and the battery can be synergistically reduced to improve the battery performance. Moreover, compared with the amount of traditional conductive agent added (currently the lowest is 1%~3%), the amount of SWCNT added in this application is 0.03%~0.10%, which greatly reduces the proportion of conductive agent and significantly increases the proportion of LFP, which is beneficial to improving the energy density of the battery cell.

[0042] In some embodiments, the specific surface area of ​​the single-walled carbon nanotubes in the positive electrode sheet satisfies BET 500≤BET≤800m2 Specifically, the lower limit of the specific surface area BET of the single-walled carbon nanotubes in the positive electrode sheet may include the following values: 500m 2 / g,550m 2 / g or 600m 2 / g, the upper limit of the specific surface area of ​​single-walled carbon nanotubes in the positive electrode sheet BET may include the following values: 800m 2 / g,750m 2 / g or 700m 2 When the BET surface area of ​​SWNTs is too small (e.g. less than 500 m 2 / g), resulting in low purity of single-walled carbon nanotubes, the presence of double-walled or multi-walled mixtures, and poor conductivity; when the BET specific surface area of ​​single-walled carbon nanotubes is too high (for example, greater than 800m 2 / g), the dispersion of single-walled carbon nanotubes is too difficult, which will lead to poor slurry stability and directly affect battery consistency; by BETing the specific surface area of ​​single-walled carbon nanotubes in the positive electrode to the above value, a richer conductive network structure can be formed under the condition of extremely low SWCNT addition, ensuring the electron and ion transmission channels on the LFP surface; in addition, sufficient coating of LFP can effectively prevent the electronic conductive network from falling off due to the volume expansion and contraction of the main material during long cycles.

[0043] In some embodiments, the diameter of the single-walled carbon nanotubes in the positive electrode sheet is 1 to 5 nm. Specifically, the lower limit of the diameter of the single-walled carbon nanotubes in the positive electrode sheet may include the following values: 1.0 nm, 1.2 nm or 1.5 nm, etc.; the upper limit of the diameter of the single-walled carbon nanotubes in the positive electrode sheet may include the following values: 5 nm, 4.8 nm or 4.5 nm, etc. In this way, its sheet diameter is much smaller than the characteristic width of other positive electrode system conductive agents (such as graphene sheet diameter>1μm, carbon black primary particle diameter>20nm, MWCNT tube diameter>10nm), thereby significantly reducing the characteristic width of the conductive agent that lithium ions need to bypass to diffuse from the LFP interface to the separator, effectively shortening the diffusion path, improving the polarization problem of the battery cell, and being beneficial to the electrical properties of the battery such as low-temperature discharge.

[0044] In some embodiments, the single-surface density of the positive electrode active material coated on the positive electrode sheet is 210±3 g / m 2 .

[0045] In some embodiments, the adhesive in the positive electrode sheet includes one or more of PVDF, PVA, PTFE and PAA. It is understood that the adhesive is not limited to the above description, and any adhesive known in the art can be used as long as the purpose of this application can be achieved.

[0046] On the other hand, the present application provides an electrode, which includes the positive electrode plate as above.

[0047] On the other hand, the present application provides a secondary battery, comprising the above-mentioned positive electrode sheet or electrode.

[0048] Specifically, the secondary battery may include but is not limited to a lithium secondary battery. The secondary battery also includes a negative electrode sheet, a separator and an electrolyte.

[0049] In the embodiment of the present application, the negative electrode sheet may include a negative electrode active material, a negative electrode binder, a negative electrode thickener and a negative electrode conductor. The negative electrode active material, the negative electrode binder, the negative electrode thickener and the negative electrode conductor are not particularly limited, and any material known in the art can be used as long as the purpose of the present application can be achieved. In some embodiments, the negative electrode binder may include at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, polystyrene butadiene copolymer, sodium carboxymethyl cellulose, polyimide, polyamide-imide, polyvinylidene fluoride and polyvinylidene fluoride. In some embodiments, the negative electrode thickener may include at least one of carboxymethyl cellulose, sodium carboxymethyl cellulose, vinyl carbonate, chloroethylene carbonate and vinyl sulfate. The negative electrode conductor may include at least one of conductive carbon black, carbon nanotubes, carbon fibers, flake graphite, Ketjen black or graphene. In one embodiment, the negative electrode binder is polystyrene butadiene copolymer (SBR), the negative electrode thickener is carboxymethyl cellulose (CMC), and the negative electrode conductor is conductive carbon black.

[0050] On the other hand, the present application provides an electronic device, which includes the above positive electrode sheet or secondary battery. Specifically, the electronic device may include but is not limited to computers, mobile phones, wearable electronic devices, vehicle-mounted terminal devices, VR devices, and other electronic terminal devices that require secondary batteries.

[0051] On the other hand, the present application provides a method for preparing a positive electrode sheet, comprising the following steps: mixing lithium iron phosphate, SWCNT, and PVDF in a weight ratio of (97.90~97.97):(0.03~0.10):2, adding NMP as a solvent, mixing and stirring evenly, and then coating the mixture on a carbon-coated aluminum foil, and obtaining the positive electrode sheet after drying, cold pressing, die-cutting and other processes.

[0052] In another aspect, the present application provides a method for preparing a secondary battery, comprising the following steps:

[0053] S1: Prepare a positive electrode sheet based on the above method;

[0054] S2: Mix the negative electrode active material, CMC, SBR, and conductive carbon black in a weight ratio of (94-97):(1.0-1.3):(1.4-1.7):1.3, add deionized water as a solvent, mix and stir evenly, and then coat the mixture on a copper foil, and obtain a negative electrode sheet after drying, cold pressing, die cutting, and other processes;

[0055] S3: stack the negative electrode sheet, separator and positive electrode sheet in order, with the separator placed between the positive and negative electrode sheets to play an isolating role, and then obtain the roll core by stacking or winding; place the roll core in a soft package and shell it, inject electrolyte after drying, vacuum package, and divide the capacity to obtain a secondary battery.

[0056] Preferably, the weight ratio of the negative electrode active material, CMC, SBR and conductive carbon black is 96:1.2:1.5:1.3.

[0057] In summary, after a large number of experiments, it was found that the amount of SWCNT added, BET and tube length distribution width can synergistically affect the conductive properties of the positive electrode sheet, and there is a complex correlation between their effects on the conductive properties. By setting the relationship values ​​between the above parameters to the aforementioned ranges of the present application, and controlling the above parameters to their respective appropriate value ranges, the battery's normal temperature (25°C) and low temperature (such as 0°C) discharge DCR can be reduced, the battery rate discharge energy efficiency is improved, the temperature rise is reduced, and the safety performance of the battery cell is improved.

[0058] The following describes the embodiments and comparative examples of the present application in combination with the above technical solutions.

[0059] The secondary batteries in the examples and comparative examples 1-2 were prepared by the following method:

[0060] 1) Preparation of positive electrode sheet: Lithium iron phosphate, SWCNT, and PVDF were mixed in a weight ratio of (97.90-97.97):(0.03-0.10):2, NMP was added as solvent, mixed and stirred evenly, and then coated on carbon-coated aluminum foil. The single-sided surface density was 210±3g / m 2 After processes such as drying, cold pressing, and die cutting, the positive electrode sheet is obtained.

[0061] 2) Preparation of negative electrode sheet: Mix the negative electrode active material, PAA, SBR and conductive carbon black in a weight ratio of 96:1.2:1.5:1.3, add deionized water as solvent, mix and stir evenly, and then coat on copper foil. The single-sided surface density is 90±1g / m 2 After drying, cold pressing, die cutting and other processes, the negative electrode sheet is obtained;

[0062] 3) Stack the negative electrode sheet, separator and positive electrode sheet in order, with the separator between the positive and negative electrode sheets to play an isolating role, and then use the stacking or winding method to obtain the roll core; place the roll core in a soft package, shell it, inject electrolyte after drying, vacuum package, and divide the capacity to obtain a secondary battery.

[0063] Comparative Example 3 Preparation of positive electrode sheet: According to the present invention, a positive electrode sheet is prepared, lithium iron phosphate, conductive carbon black, and PVDF are mixed in a weight ratio of 96.5:1.5:2, NMP is added as a solvent, and these materials are mixed and stirred evenly, and then coated on a carbon-coated aluminum foil, and the positive electrode sheet is obtained after drying, cold pressing, die cutting and other processes. The negative electrode sheet and battery assembly method in Comparative Example 3 are the same as those in the embodiment.

[0064] In addition, the test methods for each material parameter are as follows:

[0065] 1) BET of SWCNT: Use BSD-660 physical adsorption instrument to measure the specific surface area BET of SWCNT;

[0066] 2) D1, D2, and D3 of SWCNT were measured using the Truth LT3600 Plus laser particle size analyzer.

[0067] The battery performance test method is as follows:

[0068] 1) 25℃ DC internal resistance (DCR): Test the discharge DCR at 50% SOC at 25℃;

[0069] 2) 0℃ DC internal resistance (DCR): At 0℃, test the discharge DCR at 50% SOC state;

[0070] 3) 25℃ rate discharge: Test the 0.1C, 1C, 2C, and 3C discharge performance and temperature rise at 25℃, and calculate the discharge energy efficiency (with 0.1C discharge energy as 100%);

[0071] 4) 0℃ rate discharge: Test 3C discharge performance at 0℃ and calculate the discharge gram capacity.

[0072] DC internal resistance (DCR) is one of the important electrical properties of lithium-ion batteries, including charging DCR and discharging DCR. It is one of the important indicators for evaluating the performance of lithium-ion batteries, and directly affects the energy efficiency, cycle life and safety of lithium-ion batteries. Batteries with larger discharge DCR will consume more electrical energy and convert it into heat energy during discharge, resulting in greater heat generation and temperature rise, which in turn affects the safety performance of lithium-ion batteries during use. Therefore, it is very important to reduce the charge and discharge DCR of the battery cell.

[0073] The specific test results are shown in Table 1 and Table 2.

[0074]

[0075]

[0076] Based on the above Table 1, Table 2, Figure 1 and Figure 2 It can be seen that compared with Comparative Example 1, the electrode sheet resistance and discharge DCR of Examples 1 to 9 are significantly reduced, and the rate discharge energy efficiency is improved; compared with Example 3, the electrical performance of Comparative Example 2 is poor, and due to the high cost of SWCNT, even if the addition amount is increased to 0.2%, it cannot be better than the performance data of Example 3; compared with Comparative Example 3 in which 1.5% of conductive carbon black is added, the discharge DCR and rate performance of Examples 1 to 3 are significantly improved, and the conductive performance is much better than that of Comparative Example 3.

[0077] Figure 1 The SEM image of the positive electrode active material in the positive electrode sheet is shown. As shown in the figure, SWCNT is wrapped around the LFP surface to form a conductive path without obvious agglomeration.

[0078] Figure 2 The 25°C rate discharge temperature rise of Examples 1 to 3 and Comparative Examples 1 to 3 is shown. Each Example has good temperature rise optimization, among which Example 3 has the most significant improvement in temperature rise, indicating that after adding SWCNT based on the above scheme, the heat generation of the battery cell is reduced, the energy efficiency of the battery cell is improved, and the safety performance is also significantly improved.

[0079] In summary, the present application has the following beneficial effects: by adding lithium iron phosphate with uniformly distributed SWCNTs into the positive electrode plate, and clarifying the relationship between the weight proportion of SWCNTs, the tube length distribution width and the specific surface area and their corresponding value ranges, the positive electrode system conductive agent is optimized, and a three-dimensional conductive network structure with excellent conductivity can be formed in the plate, thereby reducing the plate resistance, synergistically improving the conductive performance of the positive electrode plate, reducing the normal temperature and low temperature charging and discharging DCR of the battery cell, reducing the loss of electric energy due to the internal resistance of the battery cell, improving the discharge efficiency and reducing the temperature rise, improving the discharge energy efficiency and the safety performance of the battery cell, and meeting the high-rate charging and discharging performance requirements of more than 2C.

[0080] The above description has fully disclosed the specific implementation methods of the present application. It should be pointed out that any changes made by technicians familiar with the field to the specific implementation methods of the present application do not deviate from the scope of the claims of the present application. Accordingly, the scope of the claims of the present application is not limited to the above specific implementation methods.

Claims

1. A positive electrode sheet for a secondary battery, characterized in that: The positive electrode plate includes a positive electrode current collector and a positive electrode active material coated on the surface of the positive electrode current collector, the positive electrode active material includes lithium iron phosphate and single-walled carbon nanotubes, the single-walled carbon nanotubes are dispersed in the lithium iron phosphate of the positive electrode plate, and part of the single-walled carbon nanotubes are attached to the surface of the lithium iron phosphate particles; The weight proportion A of the single-walled carbon nanotubes, the specific surface area BET of the single-walled carbon nanotubes in the positive electrode sheet, and the tube length distribution width D of the single-walled carbon nanotubes satisfy the following relationship: 1.8≤100A*BET / D≤23.5, wherein the weight proportion A of the single-walled carbon nanotubes refers to the weight proportion of the single-walled carbon nanotubes in the positive electrode sheet portion excluding the positive electrode current collector; The tube length distribution width D of the single-walled carbon nanotube is obtained by the following formula: D = (D3-D1) / D2; Wherein, D1 represents the sheet diameter corresponding to the cumulative volume proportion of the single-walled carbon nanotubes used in the positive electrode sheet in the NMP solvent reaching the first preset proportion, D2 represents the sheet diameter corresponding to the cumulative volume proportion of the single-walled carbon nanotubes used in the positive electrode sheet in the NMP solvent reaching the second preset proportion, and D3 represents the sheet diameter corresponding to the cumulative volume proportion of the single-walled carbon nanotubes used in the positive electrode sheet in the NMP solvent reaching the third preset proportion, and the first preset proportion, the second preset proportion and the third preset proportion increase in sequence; The tube length of the single-walled carbon nanotube satisfies at least one of 0.1≤D1≤1.2μm, 3≤D2≤8μm and 10≤D3≤25μm; The tube length distribution width D of the single-walled carbon nanotubes satisfies 3.4≤D≤8.3; The weight proportion A of the single-walled carbon nanotubes satisfies 0.03%≤A≤0.10%; The specific surface area of ​​the single-walled carbon nanotubes in the positive electrode sheet satisfies BET 500≤BET≤800 m 2 / g.

2. The positive electrode sheet according to claim 1, characterized in that: The diameter of the single-walled carbon nanotubes in the positive electrode plate is 1-5 nm.

3. The positive electrode sheet according to claim 1, characterized in that: The adhesive in the positive electrode plate includes one or more of PVDF, PVA, PTFE and PAA.

4. The positive electrode sheet according to claim 1, characterized in that: The weight proportion A of the single-walled carbon nanotubes, the specific surface area BET of the single-walled carbon nanotubes in the positive electrode plate and the tube length distribution width D of the single-walled carbon nanotubes satisfy the following relationship: 4≤100A*BET / D≤15.

5. The positive electrode sheet according to claim 1, characterized in that: The lithium iron phosphate in the positive electrode plate is nano lithium iron phosphate.

6. A secondary battery, characterized in that: The secondary battery comprises the positive electrode sheet according to any one of claims 1 to 4.

7. An electrode, characterized in that: The electrode comprises the positive electrode sheet according to any one of claims 1 to 4.

8. An electronic device, characterized in that: The electronic device comprises the positive electrode sheet according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Graphene / silicone / carbon nano tube composite material and preparation method and application thereof

    CN105576203A

  • Positive electrode plate and lithium ion battery

    CN106848326A